The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/jasp.12369
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant entrepreneurship from a social psychological perspective

Abstract: We examined immigrant entrepreneurship from a social psychological perspective with an emphasis on Social Identity Theory (SIT). Immigrant entrepreneurs from across Canada (N=122) completed a questionnaire about their experiences as Canadian business owners. The results showed that business decisions are, indeed, related to social psychological influences. The use of social capital, the strength of cultural and national identity, acculturation and perceived discrimination were related to decisions made through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 99 publications
(142 reference statements)
0
26
0
2
Order By: Relevance
“…Kључне речи: етничко предузетништво, етнички ресурси, миграције Проучавање односа између етницитета и предузетништва је интердисциплинарни проблем, на шта указује дисциплинарни плурализам истраживања у овој области (Robertson and Grant, 2016;Brettell and Alstatt, 2007;Schuetze and Antecol, 2006;Portes et al, 2002;Schinnar and Nayir, 2018). Ипак, посебно се истичу доприноси социологије због чега се неретко сматра да је етничко предузетништво социолошки феномен, као и да ову појаву најадекватније могу да објасне социолози.…”
Section: класични приступи и савремени теоријски модели објашњења етнunclassified
“…Kључне речи: етничко предузетништво, етнички ресурси, миграције Проучавање односа између етницитета и предузетништва је интердисциплинарни проблем, на шта указује дисциплинарни плурализам истраживања у овој области (Robertson and Grant, 2016;Brettell and Alstatt, 2007;Schuetze and Antecol, 2006;Portes et al, 2002;Schinnar and Nayir, 2018). Ипак, посебно се истичу доприноси социологије због чега се неретко сматра да је етничко предузетништво социолошки феномен, као и да ову појаву најадекватније могу да објасне социолози.…”
Section: класични приступи и савремени теоријски модели објашњења етнunclassified
“…Such a situation makes native people lack credibility to do certain ethnic business. A strong social identity may stimulate the existing network, which operates to be a highly beneficial resource when starting up a business (Froschauer, 2001;Robertson & Grant, 2016;Sequeira & Rasheed, 2006). For example, Kalnins and Chung (2006) found that the Gujarati hotel businesses in the U.S. performed better when they were geographically close to other Gujarati (Iyer & Shapiro, 1999), as it allows access to the collective information and resources that other groups could not acquire in a formal market (Arrighetti et al, 2014).…”
Section: Social Adaptationmentioning
confidence: 99%
“…Beckers & Blumberg's (2013) comparative study found that five non-Western second generation groups of immigrant entrepreneurs had achieved higher levels of sociocultural integration in society than the first generation. However, it seems that such integration did not contribute to better business prospects among four out of five groups (Beckers & Blumberg, 2013 (Robertson & Grant, 2016). Thus, to some extent, it is essential to understand two concepts.…”
Section: Sociocultural Adaptationmentioning
confidence: 99%
See 2 more Smart Citations